GERMAN FACTOR IN RUSSIAN-BRITISH FOREIGN POLICY RELATIONS IN 1910 - THE FIRST HALF OF 1914 - Konstantin Kasparyan (Гуманитарные и юридические исследования)
The article is dedicated to comprehension of German influence on Russian-British foreign policy relations in 1910 - the first half of 1914 - the period, which preceded the beginning of the First World War. Under conditions of continuously increasing confrontation between Russia and countries of the West during the last three years, which is associated with events in the Crimea and which entailed antirussian sanctions, it seems appropriate to analyze the nature of foreign policy relations of Russian empire with the largest powers of the Western world in key moments of history -in this case, at the beginning of the 20-ieth century which largely caused the outbreak of the First World War.The causes of rapprochement of Russia and Britain against the backdrop of the threat from German empire are analyzed in the article. Besides, the key factors, which did not allow German diplomacy to destroy Russian-British alliance are identiied. The study offers a comparison between foreign policy strategy of Saint-Petersburg and London. Signiicant attention is paid to the study of personality factor: the role of Nicholas II, S. D. Sazonov, George V, E. Grey, Wilhelm II, T. von Batman Holweg in the period under consideration and the level of their subjective inluence on the course of events. The article considers specific features of the co-called dynastic (or marriage) diplomacy which had been still actively referred to in the beginning of the 20-ieth century in international relationships taking into account close family ties between monarchic houses of great powers. The comprehension of this aspect allows to come to a certain conclusion: London derived the greatest beneit from the dynastic (or marriage) diplomacy as it managed to prevent restoring partnerships between Saint-Petersburg and Berlin. Besides, the study highlights some features of Russian foreign policy under conditions of maneuvering between two then leaders of the West for each of which the alliance with Russia was of primary importance.